Prototype Robot Penghisap Debu Otomatis Menggunakan Arduino Uno Dan Sensor Ultrasonic - Marcellino, Mario (Jurnal Qua Teknika, 2025)
This research aims to develop a prototype of an automatic vacuum cleaning robot using Arduino Uno and ultrasonic sensors to assist in maintaining cleanliness in spaces without the need for routine manual cleaning. The robot is designed with a mini vacuum motor that activates when the robot is turned on and moves autonomously based on data from the ultrasonic sensor, which detects obstacles in front of it. When the robot detects an object at a distance of less than 20 cm, it will reverse and turn right to avoid the obstacle. If the distance is more than 20 cm, the robot continues moving forward. The main components used include Arduino Uno as the central controller, DC motors for movement, a vacuum motor for dust collection, and a battery as the power source. Testing involving users and two technology experts demonstrated that the robot performs as expected, achieving a success rate of 94%. This result indicates that the automatic vacuum cleaning robot is effective for cleaning dry surfaces such as ceramic or wooden floors, providing a practical solution for homeowners with limited time to maintain cleanliness.